A novel risk model based on anoikis: Predicting prognosis and immune infiltration in cutaneous melanoma - Zhou, Yi; Wang, Chen; Chen, Yifang; Zhang, Wei; Fu, Zailin; Li, Jianbo; Zheng, Jie; Xie, Minghua (Frontiers in Pharmacology, 2023)
Cutaneous melanoma （CM） is a highly aggressive malignancy with a dimal prognosis and limited treatment options. Anoikis is believed to involve in the regeneration, migration, and metastasis of tumor. The exact role of anoikis‐related genes （AGRs） in CM development and progression, however, remains elusive. Four AGRs （SNAI2, TFDP1, IKBKG and MCL1） with significant differential expression were selected through Cox regression and LASSO analyses. Date for internal and external cohort validated the accuracy and clinical utility of the prognostic risk model based on AGRs. The Kaplan–Meier curve indicated that much better overall survival （OS） rate of low-risk patients. Notably, we also found that the action of ARGs in the CM was mediated by immune-related signaling pathways. Consensus clustering and TIME landscape analysis also successfully indicated that the low-risk score patients have surely excellent immune status. Moreover, the results of immunotherapy response and drug sensitivity also conformed the potential implications in informing individualized immune therapeutic strategies for CM. Collectively, the predictive risk model, which was constructed based on AGRs, provides an excellent and accurate tool for prediction for CM patient. This present research provides the rationale for the joint application of targeted therapy and immunotherapy in CM treatment, thus it had great therapeutic value and might contribute to personalized medicine therapy.